Povolání chirurg: specifická pomáhající profese - Švec, Vlastimil (Reflexe, 2022)
Title in English: Occupation surgeon: a specific helping profession The book attempts to unveil at least in part the specifics of the surgical profession. It combines the reflections of surgeons, with whom the author conducted reflective interviews, with an outsider's perspective. Being written by an educator with a wide interdisciplinary awareness, the book is likely to enlighten not only those who strive to become surgeons themselves but also readers interested in learning about other (helping) professions.